A review into the use of ceramics in microbial fuel cells. (September 2016) - Winfield, Jonathan; Gajda, Iwona; Greenman, John; Ieropoulos, Ioannis
Highlights: Ceramics an inexpensive option for building microbial fuel cells (MFCs). Viable structural material, medium for proton exchange and electrode. Maintains healthy environment for electro-active bacteria. Benefits energy harvesting. Several examples of practical implementation using ceramic MFCs. Abstract: Microbial fuel cells (MFCs) offer great promise as a technology that can produce electricity whilst at the same time treat wastewater. Although significant progress has been made in recent years, the requirement for cheaper materials has prevented the technology from wider, out-of-the-lab, implementation. Recently, researchers have started using ceramics with encouraging results, suggesting that this inexpensive material might be the solution for propelling MFC technology towards real world applications. Studies have demonstrated that ceramics can provide stability, improve power and treatment efficiencies, create a better environment for the electro-active bacteria and contribute towards resource recovery. This review discusses progress to date using ceramics as (i) the structural material, (ii) the medium for ion exchange and (iii) the electrode for MFCs.